F-117A Nighthawks - Zobel, Derek, 1983- (Minneapolis, MN : Bellwether Media, 2009)
Full-color photographs and simple text describe the features and capabilities of F-117A Nighthawks, discussing its weapons, missions, and role in the military.
Includes bibliographical references (p. 23) and index.
4.3
3-6
Keywords: F-117 (Jet attack plane) -- Juvenile literature; F-117 (Jet attack plane); Jet planes; F-117 (Jet attack plane); Jet planes; Airplanes, Military; Fighter planes; Jet planes